Heat and abrasion resistance of fly ash geopolymer mortar comprising ceramic polishing waste and cured with different conditions - Jay Bhavsar; Vijay Panchal (Electronic Journal of Structural Engineering, 2025)
The rising demand for geopolymer concrete (GPC) is associated with its lower environmental impact. GPC has significant potential for the use of industrial by-products as a geopolymer precursor. The vitrified and wall tile polishing processes produce two types of ceramic polishing wastes (CPWs): vitrified tile CPW (VCPW) and wall tile CPW (WCPW). In this study, fly ash (FA), CPW, and alkaline activators were used to make geopolymer mortar (GM). This study investigates the heat and abrasion resistance of GM cured under three curing conditions (ambient, 60°C for 24 hours, and 60°C for 48 hours). The microstructure after heat exposure was analyzed by scanning electron microscopy (SEM). In addition, the GM samples were tested for surface abrasion and compressive strength. The outcomes revealed that replacing FA with 15% CPWs improves early-age compressive strength and abrasion resistance and provided similar performance in heat resistance at 1000°C. The curing conditions strongly influenced early-age compressive strength and fire exposure performance at 500°C. The microstructure of the geopolymer shows additional geopolymerization due to heat exposure and reduced degradation of the gel. Replacing FA with 15% VCPW or WCPW enhances the heat and abrasion resistance of GM.